Use of complementary and alternative medicine in cancer patients: a prospective questionnaire-based study in an oncological outpatient clinic - König, Julia; Hofheinz, Ralf-Dieter; Kripp, Melanie (Oncology research and treatment, 2016)
Background: A questionnaire-based prospective study was conducted to evaluate the current use of complementary and alternative medicine (CAM) in a hemato-oncological outpatient clinic. Methods: A multiple-choice questionnaire was designed to assess the use of CAM in a hemato-oncological outpatient clinic. It consisted of questions on sociodemographic and general patient data, and of different kind of questions concerning the use of CAM, including disclosure rates to oncologists and general physicians. The data was analyzed with SAS and a p-value < 0.05 was considered as statistically significant. Results: 46 out of 251 patients (18%) indicated to use CAM. 62 out of all patients (25%) discussed the topic with their general physician or oncologist. Praying or nutritional supplements were the most often used type of CAM. 95 of all participating patients found that the use of CAM could be helpful. Conclusions: The findings of our monocentric study in an outpatient setting do not support the relatively high percentage of CAM users described in the current literature. Nevertheless, CAM needs to be defined more clearly, in order to increase the patients' awareness of CAM.